Study of the adhesive activity of new combined compositions based on fruit extracts Juglans - Mozhaiev, I. V.; Yevsyukova, V. Yu.; Kazmirchuk, V. V.; Torianyk, I. I.; Dovha, I. M.; Makienko, N. V.; Polishchuk, N. M.; Kyryk, D. L.; Поліщук, Наталія Миколаївна (My University, 2023)
The aim of the work is to study the effect of 3% carbon dioxide walnut extract on the adhesive properties of microorganisms.
Keywords: тези доповідей